Hubungan Strategi Marketing dalam Meningkatkan Pembiayaan Usaha Mikro Bank Syariah Indonesia KCP Pangkalan Brandan - Tiwi Oktaviani; Ahmad Fuadi (Institut Syekh Abdul Halim Hasan Binjai, 2022)
Sharia Financial Institutions as intermediary institutions between shahibul maal (owners of funds) and mudharib (who need funds), namely by collecting and distributing funds from the public effectively and efficiently. As one of the Islamic Financial Institutions that has direct contact with small communities, Islamic Banks have an important task in all aspects of people's lives in an effort to channel financing to customers so that the business carried out develops and earns profits. Microfinance is one of the development contracts for Islamic Banking products. Microfinance itself is a financing provided by Islamic banks to the public as customers to run micro or small and medium businesses. This business has an important role in supporting the economy of a country, with financing provided by Islamic banks to customers so that these activities will be able to create jobs and reduce unemployment. Financing in Islamic Banks requires marketing / marketing to sell products owned in order to meet the targets to be achieved as a way to get customers who will have a positive impact in the form of profits. There is a significant influence between marketing strategies on increasing Micro Business Financing at Bank Syariah Indonesia Kcp Pangkalan Brandan. This is evidenced from the results of the hypothesis test, namely the t test with a significance level of 0.00 because the significance level is smaller than 0.05 (0.00 < 0.05) and the tcount > t table (5.565 > 1.99254), then there is a variable influence X to variable Y. The marketing strategy carried out affects the increase in Micro Business Financing at Bank Syariah Indonesia Kcp Pangkalan Brandan by 28.5%, while the remaining 71.5% (100% - 28.5%) is influenced by other variables such as administrative costs, monthly installments, customer income, and others. There is a positive relationship between Marketing Strategy (X) and an increase in Micro Business Financing (Y), the more frequent and effective the marketing strategy is carried out by Bank Syariah Indonesia Kcp Pangkalan Brandan, the customer's decision to choose Micro Business Financing at Bank Syariah Indonesia Kcp Pangkalan Brandan.